MODERN ASPECTS OF MARKETING RESEARCH APPLICATION AS DETERMINANT OF PROMOTIONAL MIX IN BUSINESS ENTITIES FROM MILK PROCESSING INDUSTRY IN THE REPUBLIC OF MACEDONIA - Katerina BOJKOVSKA (Stefan cel Mare University of Suceava, 2018)
The basis of marketing concept refers to the fact that companies exist in order to satisfy consumers’ needs. In order to achieve its objectives and be successful, a company needs tobe aware of its customers’ wishes and preferences, so that it should gather information that could be obtained through market research. Regardless of the business they are included and performing in, the marketing managers are faced with the need to make decisions constantly, i.e. solve certain problems every day. The quality of the decision mainly depends on the quality of information they have in the moment of decision. The main objective of marketing research is to provide relevant information, increase of success and decrease of risk in company’s working and making right marketing decisions on the basis of gathered marketing information. In order to achieve certain sales level, each company should choose promotional activities by means of which it will achieve the desired effect in the most efficient way.The research study is focused onmanager’s attitude towards the utilization of marketing comunication. The objective of the research is to show the significance of marketing research in modern working conditions not only of companies in general, but of companies in milk processing industry in the Republic of Macedonia as well, because it provides significant information for the market, consumers’ needs, wishes and requests, the demand for certain type of products, influence of prices on the consumers’ decision for buying milk and dairy products, etc. Also, the objective of the research is to study the way in which promotion as part of marketing mix affects consumers’ decision making for buying certain product and significance of promotion as a factor of sales volume increase; it aims at increasing the company’s profit, as well as it takes into consideration theeffects of application of the promotional activities and improvement of competitive advantage of companies in milk industry.